2019
DOI: 10.1111/1756-185x.13696
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study on factors associated with poor work outcomes in patients with axial spondyloarthritis in Singapore

Abstract: Aim: Axial spondyloarthritis (axSpA) affects patients in the prime of their economic productivity. We aim to identify factors associated with poor work productivity in patients with axSpA in Singapore. Methods:A cross-sectional study was performed in two tertiary centers in Singapore. Consecutive adult patients ≥21 years fulfilling Assessment in SpondyloarthritisInternational Society (ASAS) 2009 criteria for axSpA were recruited. Data on social demographics, clinical, treatment modalities and patient-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
8
13
0
Order By: Relevance
“…Disease duration, BASFI and ASQoL were found to be related to work outcomes in this study, which concurs with studies done in Western (27,29) and Asia populations (28). The current study showed no significant difference was found between disease activity (such as BASDAI or ASDAS) and work outcomes, which was inconsistent with other studies (27,28) and the reason may be that only patients with BASDAI ≥4 were included in this study. However, controlling disease activity is still of importance to improve work outcomes in AS patients.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Disease duration, BASFI and ASQoL were found to be related to work outcomes in this study, which concurs with studies done in Western (27,29) and Asia populations (28). The current study showed no significant difference was found between disease activity (such as BASDAI or ASDAS) and work outcomes, which was inconsistent with other studies (27,28) and the reason may be that only patients with BASDAI ≥4 were included in this study. However, controlling disease activity is still of importance to improve work outcomes in AS patients.…”
Section: Discussionsupporting
confidence: 66%
“…Besides, many other reasons including economic setting and social security system may contribute to this difference. Factors such as age (25), ethnicity (26), disease duration, disease activity (27,28), physical function (28,29), and quality of life (28) were reported to significantly affect work outcomes in other studies. Disease duration, BASFI and ASQoL were found to be related to work outcomes in this study, which concurs with studies done in Western (27,29) and Asia populations (28).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Secondly, as this was a cross-sectional study, we were not able to determine whether patients had higher levels of PA before the onset of disease. Thirdly, smokers and patients with lower educational levels might have been over-represented in our study due to the small sample size, as the proportion of smokers and distribution of educational levels in this study differed from our previous cohorts [ 30 , 31 ]. Repeating the study with larger sample size will be needed.…”
Section: Discussionmentioning
confidence: 86%
“…1 It has a significant negative impact on quality of life and work productivity. 2 Conventional therapy, as jointly recommended by the European League Against Rheumatism (EULAR) and the Assessment of Spondyloarthritis International Society (ASAS), includes non-steroidal anti-inflammatory drugs (NSAIDs), and biologics if patients have shown inadequate response to NSAIDs. 3 However, biologics are costly, and their high cost may result in sub-optimal treatment for some patients.…”
Section: Introductionmentioning
confidence: 99%